"Hard-won joy": Equity through collaboration. Issue 1 (2nd January 2021) - Landay, Eileen; Heath, Shirley Brice
ABSTRACT: Schools, community organizations, and major cultural entities can address educational inequities by engaging parents and children in arts processes, projects, and performances. Three cases featuring work in the arts show promise in contributing to the positive academic and social development of learners across the socio-economic spectrum. Â Learning science principles stand behind the practice of shifting roles, a practice that research shows to be highly effective means of boosting learning. Two cases describe direct school-home activities in which students take on the role of creative historians and produce new types of materials for peers, family, and community members. A third case, based on principles from design research, describes Public Works, a program started in 2013 by the Public Theater in New York City. The authors summarize using four metaphors related to the learning sciences that address equity issues by constructing a robust dialectic between social responsibility and imagination.